Digital Transformation in Educational Human Resource Development in Inclusion Schools - Simatupang, Anggi Nauli; Radiana, Usman; Wicaksono, Luhur (Universitas Negeri Jakarta, 2024)
Background Digital transformation in inclusive schools is a strategic step To upgrade the quality of educational human resources. By utilizing technology effectively, schools can create learning environments that are more inclusive and adaptive to the needs of all students. Purpose This study aims to explore how digital transformation impacts the development of human resources (HR) in inclusive schools. Design/method/approach Utilizing a qualitative approach through literature review, this research synthesizes data from recent journals, books, and articles published between 2014 and 2024. Results The findings reveal that digital transformation significantly enhances HR development by providing interactive and adaptive training methods such as e-learning platforms and simulation tools, which are crucial for improving the skills of educators in inclusive settings. Additionally, digital tools facilitate flexible learning and better communication between teachers, students, and parents, thus supporting a more inclusive educational environment. However, challenges such as limited technological infrastructure, insufficient training, and regional disparities need to be addressed to fully realize the benefits of digital transformation. Contribution/value The study highlights that while digital transformation offers substantial improvements in teaching and HR development, ongoing support and resource allocation are essential for overcoming existing obstacles and maximizing its positive impact on inclusive education.